Evidence of positive influence: soft skills competence and organizational culture on innovative work behavior - Kholifah, Nur; Nurtanto, Muhammad; Kassymova, Gulzhaina K.; Subakti, Hani; Hamid, Mustofa Abi (Journal of Education and Learning (EduLearn), 2024)
This study investigates the innovative work behavior (IWB) of marine lecturers, considering work motivation (WM), organizational culture (OC), and soft skill competence (SSC). Data from 145 respondents representing ten higher education polytechnics in Indonesia were analyzed using partial least squares-structural equation modeling (PLS-SEM). Respondents answered 54 Likert-scale questions, revealing that SSC significantly shapes IWB (estimated value: 0.504), primarily through problem-solving ability. However, WM showed no significant impact on IWB, possibly due to non-influential dimensions like science, technology, environment, and society. Incorporating technological developments as moderating variables could enhance this relationship. Notably, SSC and OC exhibit crucial relationships with IWB, highlighting their importance over WM. These findings shed light on the complex dynamics influencing IWB among marine lecturers, emphasizing the significance of SSC and OC in fostering innovation in the maritime education sector.